Partial reactivation of chlorine-treated echovirus. - Young, D C (1979)
After treatment of a dispersed suspension of echovirus with HOCl, much of the lost plaque titer was restored if the treated virus was induced to aggregate by adjustment of the suspending medium to pH 4.5. This did not appear to be a repair of individual virions but rather a special kind of multiplicity-related increase in plaquing efficiency which occurred when the host cell received several of the damaged virions in a clump.